Transformasi Paradigma Kerja di Era Digital: Tinjauan Literatur Sistematis terhadap Efektivitas, Produktivitas, dan Kesejahteraan Karyawan pada Model Remote Working 2024-2025 - Saryadi Saryadi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The transition to the remote working era has reached a point of stabilization as a fundamental structure in the 2025 global employment landscape. This systematic literature review aims to evaluate the impact of remote work on employee productivity, mental well-being, and the role of Artificial Intelligence (AI) integration. By analyzing large-scale secondary data (>10,000 participants) from various authoritative databases, the study finds that productivity experienced a net increase of 13% to 22%. The primary driver is the average commute time saving of 72 minutes per day, which is converted into productive work hours. However, findings also indicate a risk of digital burnout in 69% of respondents due to an "always-on" work culture. AI integration has assisted 65% of workers in automating administrative tasks, shifting focus toward strategic work. This research concludes that the success of remote work models requires a shift in leadership style toward trust-based management and formal policies regarding the "right to disconnect.".